2007
DOI: 10.1159/000099319
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Determination of the Effect of Casein Phosphopeptide-Amorphous Calcium Phosphate Paste on the Demineralization of Bovine Dentin

Abstract: The purpose of this study was to investigate the demineralization of dentin by measuring changes in the velocity of the sonic longitudinal waves transmitted through this substrate. One group of samples was immersed in demineralization solution for 10 min twice a day and then stored in artificial saliva. Two additional groups of samples were treated with a solution of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) paste or a placebo paste without CPP-ACP before demineralization and a control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 15 publications
(9 reference statements)
1
23
0
9
Order By: Relevance
“…These results are consistent with our previous study using casein phosphopeptide-amorphous calcium phosphate to prevent demineralization. 24 The PRG filler extraction solution therefore appeared to prevent enamel demineralization. These results were supported by the absence of signs of demineralization in the PRG group according to SEM (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with our previous study using casein phosphopeptide-amorphous calcium phosphate to prevent demineralization. 24 The PRG filler extraction solution therefore appeared to prevent enamel demineralization. These results were supported by the absence of signs of demineralization in the PRG group according to SEM (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…32 In a SEM in vitro study, adding CPP-ACP to a sports drink significantly reduced the beverage's erosivity, without altering the product's taste. 7,37 The mechanisms by which CPP-ACP reduces erosive tooth wear are unclear. However the finding that CPP-ACP increases hardness of enamel eroded by cola drink implies that its erosioninhibiting potential probably involves remineralization action.…”
Section: Groupsmentioning
confidence: 99%
“…Pastes containing a complex of casein phosphopeptide (CPP) and amorphous calcium phosphate (ACP), with or without fluoride, have shown potential to prevent dental demineralization, increase remineralization in vitro (10)(11)(12)(13)(14) and to repair initial enamel caries lesions in vivo as well (15)(16)(17). It has been suggested that casein phosphopeptides (CPP) have the ability to stabilize calcium phosphate in solution by binding amorphous calcium phosphate (ACP) with their multiple phosphoserine residues, thereby allowing the formation of small CPP-ACP clusters (18).…”
Section: Introductionmentioning
confidence: 99%